Temperature-dependent phase noise properties of a two-section GaSb-based mode-locked laser emitting at 2 μm - Li, Xiang (2021)
The temperature-dependent phase noise properties of a monolithic two-section mode-locked semiconductor laser are first investigated. This is performed on a GaSb-based quantum well laser emitting at ∼2 μm. Stable mode locking operation with a fundamental repetition frequency of ∼13.3 GHz is achieved on this laser up to 60 °C. At a fixed temperature, there is no monotonous dependence of integrated jitter on the bias condition. For a given gain current or absorber voltage, there exists a corresponding optimal absorber voltage or gain current, respectively, that minimizes the integrated jitter. More important, the phase noise properties improve obviously at elevated temperatures with the lowest achievable jitter reducing obviously from 3.15 ps at 20 °C to 1.39 ps at 60 °C (100 kHz–1 GHz). We consider that the reason is reduced amplified spontaneous emission noise at high temperatures. This is confirmed by the extracted peak-to-valley ratio of the involved laser modes. We believe that this study provides an important insight into the carrier behaviors and noise performance of mode-locked semiconductor lasers, which is meaningful to their applications especially at high temperatures.